Analysis of SWOT Strategies Creativepreneurship Youtube Content Creator (Case Study of Harryware Channel Content) - Yosi Nofita Sari; Muhammad Giatman; Yuliana (Enrichment : Journal of Management, 2022)
Content competition is no longer restricted to the quality of items that emphasize each other's distinct benefits. As a result, a plan is required to increase the number of viewers. This "harryware" content provider is a company that works in the creative video sector on the YouTube platform, using the Adsense system to generate cash. The goal of this research is to build a creative strategy for video-based company growth based on the content of the Harryware YouTube channel. This study employed a qualitative research method using a descriptive case study methodology. SWOT analysis (Strength, Weakness, Opportunity, Threat) is a data analysis approach that identifies internal and external elements that create strengths and weaknesses, as well as opportunities and impediments to corporate success. The harryware youtube channel's SWOT analysis is a mechanism for defining and implementing a plan to achieve its objective and goals. The findings of this study show a substantial market potential opportunity, as seen by the proliferation of channels with comparable talks, which is relatively high, but also a significant threat, namely channel sinking from numerous new channels. Who arrive and viewers choose more popular entertainment material, posing a different danger to harryware channel video content.